Acute exacerbation of hepatitis C in hepatocellular carcinoma patients receiving chemotherapy. Issue 1 (14th June 2016) - Lin, Ji‐Wei; Chang, Ming‐Ling; Hsu, Chao‐Wei; Chen, Yi‐Cheng; Liang, Kung‐Hao; Huang, Ya‐Hui; Lin, Chen‐Chun; Yeh, Chau‐Ting
Abstract : Acute hepatitis C exacerbations can occur in cancer patients carrying hepatitis C virus (HCV) when receiving systemic chemotherapy. However, clinical studies evaluating these complications remain rare due to the lack of clinically proven effective and tolerable anti‐HCV treatments at late cancer stages. Furthermore, no data were available regarding hepatitis C exacerbation in advanced hepatocellular carcinoma (HCC) patients receiving chemotherapy. To address this issue, 48 patients with HCV‐related advanced HCC, who underwent systemic chemotherapy using 5‐ fluorouracil, cisplatin, and mitoxantrone from 2008 to 2014 were analyzed. Nine patients developed acute hepatitis exacerbations defined by HCV‐RNA elevation ≥10‐fold and alanine transaminase (ALT) elevation ≥5‐fold of the upper normal limit. Six were genotype 1b and 3 were genotype 2. Three patterns of clinical courses were observed including single episode of exacerbation (n = 5), fluctuated flares (n = 3), and delayed exacerbation (n = 1). Hepatic failure developed in five patients. Patients with acute exacerbations were less likely to have pretreatment ascites (11.1% vs. 53.8%; P = 0.028) and displayed a lower baseline ALT (44.1 ± 28.5 U/L vs. 72.6 ± 19.2 U/L; P = 0.007). Paradoxically, despite a high risk of hepatic failure, occurrence of hepatitis C exacerbation was associated with a favorable overall survival ( P = 0.027; 22.8 vs. 5.4 months). In conclusion, hepatitis C exacerbation can occur in HCC patients receiving chemotherapy, leading to liver failure. However, the flare was associated with a better overall survival, possibly due to its association with a better baseline liver function. J. Med. Virol. 89:153–160, 2017 . © 2016 Wiley Periodicals, Inc.